The Role of 8% Branched Amino Acids (BCAA) in Patients with Hepatic Encephalopathy: 8% Branched Amino Acids in Patients with Hepatic Encephalopathy - Shahzad, Arslan; Quddus, Muhammad Abdul; Manzoor, Amna; Munawar, Ruksana; Saeed, Rizwan; Mumtaz, Hamayun (Pakistan Journal of Health Sciences, 2025)
Hepatic Encephalopathy (HE) is a neuropsychiatric disorder caused by liver dysfunction, commonly seen in cirrhosis or acute liver failure. Objective: To address the safety and efficacy of branched-chain amino acids (BCAA) solution in patients with HE. Methods: This retrospective study was performed at the Sheikh Khalifa Bin Zayed Al Nahyan Hospital, CMH Rawalakot, Azad Kashmir, Pakistan. Data from patients fulfilling the eligibility criteria during the study span from February 2022 to August 2024 were analyzed. The inclusion criteria were adults aged 18-70 years, diagnosed cases of cirrhosis of the liver, and admitted with HE. The BCCA group was given 8% BCCA solution administered through intravenous (IV) transfusion. Patients receiving any other treatments were categorized as conventional treatment. Psychometric hepatic encephalopathy score (PHES), serum ammonia levels, duration of hospitalization, treatment-related adverse events, and mortality were documented. Results: 467 patients were analyzed, the median age was 54.00 (48.00-63.00) years, and 280 (60.0%) were male. 315 (67.5%) received IV BCAA, while the remaining 152 (32.5%) received conventional therapy. Patients in the BCAA group showed a significant improvement in PHES scores, (-2.1 ± 1.9 vs. -4.6 ± 2.2, p=<0.001), reduction in serum ammonia levels (45.3 ± 8.1 vs. 56.2 ± 10.8 µmol/L, p<0.001), mean duration of hospitalization (8.9 ± 3.7 vs. 10.1 ± 4.5 days, p=0.002), and mortality (3.8% vs. 9.2%, p<0.001). In the BCAA group, 8 (2.2%) patients experienced mild gastrointestinal discomfort, and 4 (1.3%) patients reported transient dizziness.Conclusions: Intravenous 8% BCAA solution effectively enhances cognitive function, lowers serum ammonia, shortens hospitalization, and reduces mortality in hepatic encephalopathy patients.